2020
DOI: 10.1021/acsnano.0c02633
|View full text |Cite
|
Sign up to set email alerts
|

Liver-Targeted siRNA Lipid Nanoparticles Treat Hepatic Cirrhosis by Dual Antifibrotic and Anti-inflammatory Activities

Abstract: Previous studies on the treatment of hepatic cirrhosis have been focusing on how to inhibit liver fibrosis, while ignoring liver inflammation, a key and underlying factor that promotes cirrhosis. High mobility group box-1 (HMGB1) protein, a pro-inflammatory factor and fibroblast chemokine, can promote the proliferation of hepatic stellate cells (HSCs) and the development of hepatic inflammation and fibrosis, playing a key role in cirrhosis formation. In this study, we prepared pPB peptide (C*SRNLIDC*)-modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 43 publications
(69 reference statements)
1
46
0
Order By: Relevance
“…This study did not dwell deep into the mechanistic aspects, and we could not analyze the direct effect of this peptide against hepatic stellate cells (HSCs). Recently, Zhang et al reported that HSC-targeted lipid nanoparticles loaded with HMGB1-siRNA attenuated liver fibrosis and inflammation [ 36 ]. The difference between this study and ours is that while Zhang et al used HMGB1 knockdown, we used the modified HMGB1 peptide lacking box B lesion for the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This study did not dwell deep into the mechanistic aspects, and we could not analyze the direct effect of this peptide against hepatic stellate cells (HSCs). Recently, Zhang et al reported that HSC-targeted lipid nanoparticles loaded with HMGB1-siRNA attenuated liver fibrosis and inflammation [ 36 ]. The difference between this study and ours is that while Zhang et al used HMGB1 knockdown, we used the modified HMGB1 peptide lacking box B lesion for the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The drug delievery system prolonged circulation half-life of IFNγ and decreased its side effects in fibrotic livers. Recently, Zhang et al (2020) constructed pPB peptide-modified stable nucleic acid lipid NPs loading HMGB1 (High mobility group box-1)-siRNA (HMGB1-siRNA@SNALP-pPB) to effectively treat liver cirrhosis by their dual antifibrotic and anti-inflammatory abilities ( Figure 3 ). HMGB1 protein is known as a fibroblast chemokine and pro-inflammatory factor, which promotes the proliferation of HSCs and facilitates hepatic inflammation and fibrosis.…”
Section: Nanodrug Delivery System Targeting Hepatic Stellate Cellsmentioning
confidence: 99%
“…FIGURE 3 | Schematic diagram of the HMGB1-siRNA@SNALP-pPB nanoparticle targeting HSCs to silence HMGB1 to show antifibrotic and antiinflammatory effects for hepatic cirrhosis(Zhang et al, 2020).…”
mentioning
confidence: 99%
“…HMG1, a non-histone protein discovered years ago, is widely distributed in tissues such as the liver, brain and lymphatic system. With the discovery of its pro-inflammatory effect, HMG1 has become important in critical medical research in recent years [8]. IL-6 performs a large variety of functions and is mainly produced by immune cells but can also be expressed by hepatocytes.…”
Section: Introductionmentioning
confidence: 99%